Travel Busins Strategy Using The Business Model Canvas Approach ( Case Study : Sofyan Travel ) - M. Hafiz Farhan; Fauzi Arif Lubis; Ahmad Muhaisin B. Syarbaini (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
Sofyan Travel, a 15-year-old travel transportation business, has faced significant challenges due to the COVID-19 pandemic and increased digital competition. This study uses a qualitative case study approach to analyze Sofyan Travel's business strategy using the Business Model Canvas (BMC). The results show that the BMC approach enables the company to identify strengths, weaknesses, opportunities, and threats through nine key elements, such as customer segmentation, value proposition, distribution channels, and cost structure. The strategy focuses on personalized service, operational efficiency, service digitalization, and strategic partnerships. The implementation of the BMC has proven effective in increasing business competitiveness and sustainability by adapting conventional models to modern market needs. These findings reinforce the relevance of the BMC as an innovative tool for designing and managing travel businesses in an adaptive and customer-value-oriented manner. Keywords: Business Model Canvas, business strategy, travel, competitiveness